Incident Management Systems Are Essential for Effective Coordination of Large Disease Outbreaks: Perspectives from the Coordination of the Ebola Outbreak Response in Sierra Leone - Olu, Olushayo Oluseun; Lamunu, Margaret; Chimbaru, Alexander; Adegboyega, Ayotunde; Conteh, Ishata; Nsenga, Ngoy; Sempiira, Noah; Kamara, Kande-Bure; Dafae, Foday Mohamed (Frontiers in Public Health, 2016)
Background Response to the 2014–2015 Ebola virus disease (EVD) outbreak in Sierra Leone overwhelmed the national capacity to contain it and necessitated a massive international response and strong coordination platform. Consequently, the Sierra Leone Government, with support of the international humanitarian community, established and implemented various models for national coordination of the outbreak. In this article, we review the strengths and limitations of the EVD outbreak response coordination systems in Sierra Leone and propose recommendations for improving coordination of similar outbreaks in the future. Conclusion There were two main frameworks used for the coordination of the outbreak; the Emergency Operation Center (EOC) and the National Ebola Response Center (NERC). We observed an improvement in outbreak coordination as the management mechanism evolved from the EOC to the NERC. Both coordination systems had their advantages and disadvantages; however, the NERC coordination mechanism appeared to be more robust. We identified challenges, such as competition and duplication of efforts between the numerous coordination groups, slow resource mobilization, inadequate capacity of NERC/EOC staff for health coordination, and an overtly centralized coordination and decision-making system as the main coordination challenges during the outbreak. Recommendations We recommend the establishment of EOCs with simple incident management system-based coordination prior to outbreaks, strong government leadership, decentralization of coordination systems, and functions to the epicenter of outbreaks, with clear demarcation of roles and responsibilities between different levels, regular training of key coordination leaders, and better community participation as methods to improve coordination of future disease outbreaks.